2000
DOI: 10.1016/s0022-3697(99)00272-3
|View full text |Cite
|
Sign up to set email alerts
|

Theory of ferroelectrics: a vision for the next decade and beyond

Abstract: In the last ten years significant advances have been made in our understanding and ability to compute and predict properties of ferroelectrics and piezoelectrics using fundamental physics. Phase diagrams, electromechanical and elastic properties, and effects of defects and surfaces are now amenable to computation. Most importantly, new techniques have been developed, and new understanding of the meaning of polarization in dielectrics has been developed. Prospects for the future are discussed. Nb23 O 3 -PbTiO 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 57 publications
1
57
0
1
Order By: Relevance
“…Consequently, this alteration results in the structural order-disorder. Studies on intermediate levels 5 and the order-disorder 43 showed a decrease in the optical band gap according to the structural organization. For the decrease in the optical band gap, three forms of displacement of the VB and CB can be proposed: ͑1͒ an increase in the VB energy and a decrease in the CB energy; ͑2͒ the VB energy remains constant and the CB energy decreases; and ͑3͒ an increase in the VB and CB energy remains constant.…”
Section: 16mentioning
confidence: 99%
“…Consequently, this alteration results in the structural order-disorder. Studies on intermediate levels 5 and the order-disorder 43 showed a decrease in the optical band gap according to the structural organization. For the decrease in the optical band gap, three forms of displacement of the VB and CB can be proposed: ͑1͒ an increase in the VB energy and a decrease in the CB energy; ͑2͒ the VB energy remains constant and the CB energy decreases; and ͑3͒ an increase in the VB and CB energy remains constant.…”
Section: 16mentioning
confidence: 99%
“…This follows the spirit of a view of PZN-PT and PMN-PT as large-strain PbTiO 3 -based systems that have been chemically "engineered" to make them marginally stable in the rhombohedral phase. 43 We do something very similar, but using a theoretical manipulation that avoids the unnecessary complexities of the real alloy systems.…”
Section: Field-induced Structural Phase Transitionsmentioning
confidence: 99%
“…PMN exhibits frequency dependent dielectric dispersion characteristic of relaxors and has a large, broad peak at around room temperature [1]. Relaxors are disordered over various length scales, and a multiscale approach involving a combination of various techniques including quantum mechanical, atomistic and continuum approaches [2][3][4] is required. The disorder in PMN gives rise to anomalies in nearly all observed properties including diffuse scattering, dynamical properties and the important applications coupled with their rich physics have resulted in extensive theoretical and experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…These can be used to derive interatomic potentials [2][3][4] and effective Hamiltonians which in turn can be employed to study the disordered solid solution PMN-PT over larger length and time scales. Our calculations reveal that ordered PMN supercells are ferroelectric.…”
Section: Introductionmentioning
confidence: 99%